1995
DOI: 10.1056/nejm199506153322402
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Treatment of Osteopetrosis with Recombinant Human Interferon Gamma

Abstract: Long-term therapy with interferon gamma in patients with osteopetrosis increases bone resorption and hematopoiesis and improves leukocyte function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
137
1
6

Year Published

1996
1996
2013
2013

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 258 publications
(145 citation statements)
references
References 18 publications
1
137
1
6
Order By: Relevance
“…22 In selected cases, surgical decompression of the optical nerve might be indicated to prevent further deterioration awaiting HSCT. 23 In some patients, calcitriol in high dosages 11 or interferon gamma 12 might slow the progression of the disease. Improvement of haematopoiesis can be achieved with prednisone.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…22 In selected cases, surgical decompression of the optical nerve might be indicated to prevent further deterioration awaiting HSCT. 23 In some patients, calcitriol in high dosages 11 or interferon gamma 12 might slow the progression of the disease. Improvement of haematopoiesis can be achieved with prednisone.…”
Section: Discussionmentioning
confidence: 99%
“…10 Treatments with approaches other than HSCT such as corticosteroids, high doses of calcitriol (vitamin D 3 ) and interferon-g, have been disappointing. [11][12][13][14] We report the results of HSCT in 122 patients treated in Europe, Costa Rica and Saudi Arabia, including the follow-up of HSCT survivors from 1994.…”
mentioning
confidence: 99%
“…As a result of its numerous functions, recombinant human IFN-γ (rhIFN-γ) is finding increasing therapeutic applications. In the treatment of chronic granulomatous disease [6][7][8][9], and in severe malignant osteopetrosis [10,11], rhIFN-γ has clinically accepted beneficial effectiveness. Additionally, in the almost uniformly fatal progressive fibrosing lung disease, idiopathic pulmonary fibrosis (IPF), a recent metaanalysis has concluded that rhIFN-γ treatment is associated with reduced mortality [12].…”
Section: Introductionmentioning
confidence: 99%
“…Other neurological manifestations of osteopetrosis may include strabismus, facial paralysis, deafness, trigeminal nerve involvement and anosmia. 17 Most of these result from direct compression of cranial nerves and are most pronounced in patients with early disease onset. 20 Both of our patients only showed severe visual impairment with bilateral optic nerve subatrophy, which stabilized after BMT.…”
Section: Discussionmentioning
confidence: 99%
“…Each of these therapies, such as steroids, ␥ interferon, hydroxyvitamin D 3 alone or in combination, has produced limited and transient improvement. [14][15][16][17] The only curative therapy reported is allogeneic BMT. 18,19 During the last 15 years, almost 100 BMTs for osteopetrosis have been reported.…”
Section: Discussionmentioning
confidence: 99%